Interactive Learning Objects: Support tools for the teaching of Natural Sciences - Sandoval, Elsa María Figueroa; Gámez, María Rodríguez (International Journal of Psychosocial Rehabilitation, 2020)
The use of tools for virtual teaching is more frequent every day, this trend is driven by the range of available technological resources, which allows cost reduction and allows to avoid some restrictions such as mobility restrictions that some students present, within Information and communication technologies, didactic resources called interactive learning objects are used, these play an important role for the support of teachers than various teaching modalities. The research aims to characterize interactive learning objects and their application for the development of skills in the area of natural sciences in high school students. This research was developed using the Desk Research methodology, based on the review of theoretical concepts on learning objects and their subsequent analysis that allowed determining the advantage of their use in natural science subjects. Finally, it was possible to determine how Interactive Learning objects can contribute in the processes of inquiry, understanding and interpretation of the results required in the study of different natural phenomena and the theme of natural sciences, in addition to the advantages for the realization of the experiential experimentation using multimedia resources.